MARTABAT PEREMPUAN DALAM KONTEKS MULIERIS DIGNITATEMDAN IMPLIKASINYA TERHADAP ISU KESETARAAN GENDER - Benamen, Domanika Lusia; Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
This research examines the encyclical Mulieris Dignitatem and its implications for women's dignity and gender equality. The research utilizes library materials as the primary source of data and references. Mulieris Dignitatem emphasizes that both men and women are created in the image of God and have inherent dignity. This concept of women's dignity is relevant in addressing issues of discrimination, domestic violence, and limited rights for women in politics and society, particularly in relation to Catholic values. Furthermore, the concept of women's dignity can serve as an inspiration to empower women in various domains of life, including the family, church, and society. Overall, Mulieris Dignitatem provides a foundation for evaluating and addressing gender inequality while promoting women's rights and roles in different aspects of life. Keywords: Women's Dignity, Gender Equality, and Mulieris Dignitatem